Intra-articular Myxoma Arising from the Scapholunate Ligament: A Rare Cause of Dorsal Wrist Swelling - Eseonu, Onyedikachi I.; Thomas, Roshin (Journal of Hand and Microsurgery, 2019)
The differential diagnosis of a dorsal wrist swelling includes ganglion, lipoma, cutaneous tumors, and benign peripheral nerve sheath tumors, with ganglions being the most common. We present the case of a myxoma arising from the dorsal scapholunate ligament mimicking a dorsal wrist ganglion. Volar wrist joint myxomas have been previously reported, but this is the first report of a myxoma arising from the dorsal side of the wrist joint.
Keywords: intra-articular Myxoma; dorsal wrist ganglion; wrist joint; soft tissue neoplasms